ANALISIS FAKTOR TERHADAP UPAYA MENUMBUHKAN MINAT BACA SISWA - Andi Batara Indra; Muh. Nurdin; Fajrul Ilmy Darussalam; Jamiu Temitope Sulaimon (CARAKA, 2021)
Factor analysis of effort to Grow Students’ Reading Interest. This study aims to analyze the factors that can grow students’ reading interest, especially at junior high school and senior high school levels. This study is a descriptive qualitative research in which data sources are contained in junior and senior high schools of Metro School Makassar. The result of this study shows that School Literacy Movement (SLM) reading for five teen minutes before class is a less effective application in an effort to foster ethics and students’ reading interests. In addition, this study found nine factors that can affect students reading interest: (1) Leaders or teachers, (2) time allocation for reading, (3) type of reading, (4) reading place or library, (5) availability of books, (6) financial or the economic state of parents, (7) parents support, (8) Book store, (9) motivation to increase reading interest.